Implementasi Sistem Informasi Virtual Tour Pada Orchid Forest - Maya Destriani; Tazkia Salsabila Ardan; Bagus Ali Akbar; Cecep Nandang Sudiarno (JATISI, 2025)
The virtual tour information system at Orchid Forest is designed to provide an interactive and immersive digital tour experience. The system allows visitors to explore the Orchid Forest virtually, with features designed to improve accessibility for potential visitors who are unable to attend in person, while promoting the destination to a wider audience. The virtual tour feature includes an interactive exploration of various tourist locations with a 360-degree panoramic view. The development of this system begins with an analysis of functional and non-functional needs. Functional needs include virtual tour creation, multimedia integration (360° photos, video, and audio), interactive navigation, and interactive information features that describe each location. Non-functional needs such as access security, performance, and scalability are also considered in system design. The technologies used include React.js for the development of interactive and responsive user interfaces. For the display of 360-degree panoramic images and 3D elements, Photosphere Viewer and Three.js are used. On the backend side, the system is built using GraphQL and Express.js, with the MariaDB database to support fast and efficient data interaction. This combination of technologies provides a smooth user experience as well as supports scalability for further development. The result of the development of this system is a virtual tour platform that provides a realistic and interactive visual experience. This system is expected to increase tourist engagement and interest in the Orchid Forest, both through physical visits and virtual tour experiences.